2017
DOI: 10.1111/jocn.13922
|View full text |Cite
|
Sign up to set email alerts
|

The impact of aspiration pneumonia and nasogastric feeding on clinical outcomes in stroke patients: A retrospective cohort study

Abstract: Aims and objectives: To determine presence of clinical complications related to dysphagia and to explore their operational outcomes.Background: Dysphagia is a common complication of stroke. The management of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 45 publications
0
31
0
2
Order By: Relevance
“…Kalra et al [31] and Kalra et al [32] used the same RCT data. Study designs included RCTs (30%) [15,[31][32][33], prospective (20%) [13,34] and retrospective (40%) [35][36][37][38] observational studies and one quasi-experimental design [39]. Europe hosted 55% of studies [15,[31][32][33][34]37], Australia 27% [13,36,38] and Japan 18% [35,39].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Kalra et al [31] and Kalra et al [32] used the same RCT data. Study designs included RCTs (30%) [15,[31][32][33], prospective (20%) [13,34] and retrospective (40%) [35][36][37][38] observational studies and one quasi-experimental design [39]. Europe hosted 55% of studies [15,[31][32][33][34]37], Australia 27% [13,36,38] and Japan 18% [35,39].…”
Section: Resultsmentioning
confidence: 99%
“…Warusevitaine et al [15] and Langdon et al [13] reported at 21 days and 30 days, respectively. Schwarz et al [38] did not report the period of diagnosis. Marked variation in study design and reporting of participant characteristics prohibited meta-analysis.…”
Section: Diagnosis and Frequency Of Sapmentioning
confidence: 98%
See 2 more Smart Citations
“…Various mechanisms underlying the development of SAP have been identi ed, in addition to stroke-induced immunosuppression, dysphagia, poor respiratory muscle strength, decreased pulmonary function and respiratory center dysfunction after brain injury also play important roles [5][6][7][8][9][10]. Among them, oral hygiene is often overlooked.…”
Section: Introductionmentioning
confidence: 99%